Growth of African Girls during Adolescence in Varied Environmental Conditions - Kolasa, Ewa (Anthropological Review, 2022)
Using the data found in literature and collected by the author, the growth of girls representing various environments and social strata from Zaire, Rwanda, Uganda, Nigeria, Gambia and Somalia is discussed, taking into account body height and weight and the age at menarche. An attempt is made to assess the secular end in the development of Zairean and Nigerian girls.